Synaptic plasticity and the neurobiology of learning and memory - Benfenati, Fabio (Acta Biomedica Atenei Parmensis, 2007)
Learning and memory are fundamental higher brain functions that allow the individual to adapt to the environment, to build up his own history as a unique creature, to widen the personal cultural background and, ultimately, the population culture. In this review, we will briefly examine the cellular and molecular mechanisms that contribute to the various forms of memory that include short- and long-term memory as well as unconscious and conscious memory. Although in mammals various brain areas participate in distinct forms of memory, the molecular and cellular mechanisms of very simple to complex forms of learning and memory are extremely conserved across evolution from molluscs to man and among various forms of memory and consist in short-to-long lived rearrangements in synaptic efficiency and in the structure of neuronal networks.